Determinan Risiko Kredit Bank Umum di Indonesia - Fransiska, Welda; Ismanto, Hadi (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The banking industry plays an important role in the stability of the Indonesian financial system. This study examines the effect of capital adequacy, bank efficiency, credit growth, and liquidity on credit risk in commercial banks listed on the Indonesia Stock Exchange (IDX). Using panel data regression analysis with the Fixed Effect Model approach on secondary data for the period 2019 to 2023, with samples obtained through saturated sampling techniques. The results showed that only liquidity has a significant positive effect on credit risk, which indicates that a high liquidity ratio can increase credit risk if not managed properly. Capital adequacy, bank efficiency, and loan growth did not have a significant effect, which means capital adequacy and operational efficiency may not be directly related to credit risk.